Radial multi-echo bSSFP and IDEAL chemical shift separation in k-space for high-speed 3D hyperpolarized 13C metabolic MRI - Wang, Zirun; Grashei, Martin; Fischer, Johannes; Sühnel, Sandra; Setzer, Nadine; Awenius, Marcel; Korzowski, Andreas; Özen, Ali C.; Zaitsev, Maxim; Bock, Michael; Schilling, Franz; Schmidt, Andreas B.; et al. (Magnetic resonance in medicine, 2025)
Purpose Hyperpolarized (HP) carbon-13 (13C) MRSI provides real-time information about metabolic processes but lacks high temporal and spatial resolution. This study introduces a multi-echo-balanced steady-state free precession (ME-bSSFP) method with a 3D radial readout trajectory in a spiral phyllotaxis pattern as a method for non-Cartesian HP 13C MRSI that allows for flexible reconstruction with high spatiotemporal resolution. Methods The approach uses ME-bSSFP with iterative decomposition of echo asymmetry and least-squares estimation (IDEAL) for separating 13C metabolite signals. The method was evaluated using thermally polarized 13C-enriched phantoms and in vivo experiments in healthy rats injected with HP [1-13C]pyruvate. Results The method successfully acquired and separated thermally polarized and HP 13C metabolite signals, demonstrating its versatility and effectiveness. This approach allows for the extraction of high temporal- or high spatial-resolution 3D MRI from the same measurement. In vivo, dynamic HP metabolite intensities were extracted at a temporal resolution of 16 ms, and dynamic 3D metabolite images were generated with an isotropic FOV of 356 mm and a spatial resolution of 5.56 mm in 4.8 s. Conclusion The proposed radial ME-bSSFP method with iterative decomposition of echo asymmetry and least-squares estimation decomposition provides a flexible, efficient, and robust approach for HP 13C MRSI. It opens new possibilities for monitoring metabolic processes with unprecedented temporal resolution, generating dynamic 3D metabolite maps, and applying rapid acquisition and undersampling schemes. The method's ability to optimize imaging temporal resolution and facilitate kinetic modeling paves the way for innovative applications in dynamic HP metabolic MRI.
Im Titel erscheint die 13 hochgestellt
Online verfügbar: 28. Juli 2025
Gesehen am 10.12.2025